2021
DOI: 10.22270/ujpr.v6i1.535
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Conjunctivitis of Adults: Causes and Ophthalmic Antibiotic Resistance Patterns for the Common Bacterial Isolates

Abstract: Background: Bacterial conjunctivitis is often observed in newborns as well as in other age groups. It has been associated with several organisms that differed in their relative importance and varied in their response to ophthalmic antibiotics. Objectives: The aim of this study was to investigate bacterial conjunctivitis of adult patients by determine the specific bacterial causes and determine the  ophthalmic antibiotic resistance patterns for the bacterial isolates from conjunctivitis patients in Sana’a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…The proportion of children in the age group 6-9 years was 58.9%, while children in the age group 10-12 years constituted 41.1% of the total. The crude prevalence of active trachoma was 9.3% in this study (Table 2), which is slightly similar compared to previous studies by Al-Shamahi et al In Bajaj, and Sana'a City (10.93%, 9.1% respectively) in 2020 as well as by Thabit et al 2018 in Al-Dahlia, Al-Hodeidah, Al-Jaws, Hadhramaut, Hajjam, Ibb, Lahj, Marib and Taiz (9%) [2,[3][4][5][6][7][8][9][10][11][12][13][14][15]. The result of this study showed that children aged 6-9 years had a rate equal to 10.5% and it was slightly higher than the rate of 10-12 years (7.7%) but the difference was not significant (p = 0.19) (Table 2).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The proportion of children in the age group 6-9 years was 58.9%, while children in the age group 10-12 years constituted 41.1% of the total. The crude prevalence of active trachoma was 9.3% in this study (Table 2), which is slightly similar compared to previous studies by Al-Shamahi et al In Bajaj, and Sana'a City (10.93%, 9.1% respectively) in 2020 as well as by Thabit et al 2018 in Al-Dahlia, Al-Hodeidah, Al-Jaws, Hadhramaut, Hajjam, Ibb, Lahj, Marib and Taiz (9%) [2,[3][4][5][6][7][8][9][10][11][12][13][14][15]. The result of this study showed that children aged 6-9 years had a rate equal to 10.5% and it was slightly higher than the rate of 10-12 years (7.7%) but the difference was not significant (p = 0.19) (Table 2).…”
Section: Resultssupporting
confidence: 89%
“…No studies of trachoma have been done in the Bani Matter area before. However, there are a limited number of studies on the prevalence and determinants of eye infection in general and trachoma in particular in Yemen [6][7][8][9][10][11][12]. Therefore, the region needs further research to identify the groundwork to reduce the burden of trachoma, especially at the community level that helps government and implementing partners make an evidencebased decision in promoting and providing quality care.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that it is possible to eliminate blinding trachoma by apply an integrated package of interventions -the so-called "safe strategy" which means: surgery for trachomatous trichiasis, treatment with antibiotics to clear an ocular infection; facial hygiene to decrease the transmission of chlamydia trachomatis in the eyes; and improving the environment, especially improving access to water and sanitation [1][2][3][4][5][6][7][8][9][10][11][12]. It has been shown that antibiotic treatment for people with trachoma helps prevent the disease from spreading in the community.…”
Section: Introductionmentioning
confidence: 99%
“…According to estimates by the World Health Organization (WHO) and United Nations report, deaths due to antimicrobial resistance could increase with the time 4, 5 . Nowadays, antimicrobial resistance (AMR) is a major public health threat, 6,7 and antimicrobial resistance bacteria in different hospital departments are increasing dramatically all over the world and in Yemen this problem is more extensive and complex [8][9][10][11][12][13][14][15][16][17][18][19][20] . As for some details of the previous work in Yemen, these studies mostly focused on studying the sensitivity to antibiotics for each bacteria separately 8-20 , while the current study studied the resistance to all bacterial isolates, and the current study also identified the temporal correlation of the rate of increase in the prevalence of resistance of bacterial isolates to the antibiotics used in the study area.…”
Section: Introductionmentioning
confidence: 99%